A leap for public health - Amar, Daud Iskandar Abdullah *; Ser, Hooi Leng *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
World No Tobacco Day 2023 (May 31) underscores the need for "Better control and governance". This theme is especially pertinent to Malaysia in tackling the ecigarette issue.